Integration of Islamic Values and Local Culture in Early Childhood Education Curriculum - Sholeh, Muh Ibnu; Nur'azah; Habibulloh, Muh; Al Farisy, Fakhruddin; Munif; Ab Rahman, Siti Fatinnah binti (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2025)
Islam-based Early Childhood Education (PAUD) plays a crucial role in shaping children's character and identity by integrating Islamic values with local culture. This study aims to analyze how Islamic values and local culture are incorporated into the PAUD curriculum, identify implementation strategies, and examine the challenges and opportunities involved. Additionally, it explores the impact of this integration on children's character and identity development while providing recommendations for educators and policymakers to enhance the effectiveness of Islam-based early childhood education. This research employs a literature study method, analyzing various sources related to the PAUD curriculum, Islamic values, and local culture. The data analysis approach includes data reduction, classification, and interpretation. The findings indicate that integrating Islamic values such as tawhid, noble character, and worship with local cultural values such as community cooperation (gotong royong), love for the homeland, and mutual respect can create a holistic and contextual curriculum. This curriculum not only supports children's intellectual development but also fosters strong character and a deep sense of identity. However, challenges arise in aligning local cultural values with Islamic teachings and addressing resource limitations, particularly among educators who may not fully grasp the concept of this integration. Despite these challenges, the integration of Islamic values and local culture positively impacts children's character development and strengthens community participation in the educational process. To address these challenges, this study recommends developing a more flexible curriculum and enhancing educator capacity. These efforts will contribute to producing a generation that is intelligent, of noble character, and deeply rooted in its cultural identity.